THE INFLUENCE OF CORPORATE DISCLOSURE LEVEL ON COST OF EQUITY CAPITAL: EVIDENCE FROM INDONESIA - Angela Tamara; Yanthi Hutagaol (Journal of Applied Finance & Accounting, 2013)
This research investigates the level of corporate disclosure in Indonesia and how corporate disclosure may influence company’s cost of equity capital. Moreover, this research is also wanted to investigate the profile of corporate disclosure in Indonesia.The samples used in this research are companies that are listed in LQ-45 from 2006 to 2010. The corporate disclosure information is derived from the annual report. Moreover, related information required are also extracted from annual report, such as leverage, total asset and auditor quality. For data analysis, this research will employ a multiple regression to determine the association among variables. The result shows the disclosure level in Indonesia is actually affected cost of equity capital even though the level of significant is considered as low. As the conclusion, although most of companies does not disclosed information as the expected number of regulation, Indonesia capital market still can be considered as semi strong since the information that are available for public are actually affecting investors decision on investment.